Formation and distribution of water masses on the shelf and continental slope around Antarctica - A. V. Klepikov; N. N. Antipov (Лëд и снег, 2015)
Field studies of the last decades show that the structure and characteristics of the waters on the continental shelf of Antarctica have significant spatial differences. During the IPY 2007/2008 and post-IPY period the oceanographic sections were made from the AARI research vessels in the Prydz Bay, Amundsen and Bellingshausen Seas. Sections with high horizontal resolution (~2–3 miles between stations) at the continental slope allowed us to obtain a detailed picture of the water structure in the area of interaction of shelf and deep ocean water – at the Antarctic Slope Front. It is shown that the principal difference in the water characteristics and the front structure between the seas is determined by the peculiarities of large-scale circulation and the physical-geographical features of the regions (shelf and continental slope parameters, coastline configuration, presence and size of the ice shelves). Using modern and historical data, it is shown that the most fundamental characteristic, dividing the Antarctic shelf into two regions, is the presence (or absence) in the area of the Antarctic Shelf Water which usually occupies the bottom layer of the water column and has the temperature close to the freezing point. On all shelves of the East and, partly, the West Antarctica (from the Weddell Sea to the Ross Sea, inclusive), this water mass was found having different volumes and different salinities. On the shelves of most part of West Antarctica (in the Amundsen and Bellingshausen Seas and at the western shelf of the Antarctic Peninsula) the shelf water is not found. The consequence of these features is fundamentally different role of these two regions in the processes that affect the climate processes, namely, the formation of Antarctic Bottom Water and the role of warm Circumpolar Deep Water in the melting of the ice shelves.